Al-Dawr Al-Lughawi fi Al-Tafsir (Dirasah Manhajiyah fi Tafsir Ruh Al-Bayan) - Erizal Ilyas (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The author of this interpretation - may God have mercy on him - did not leave any of the verses of the Noble Qur’an without explaining verse after verses and clarifying clearly in all the existing vocabulary of the verses of the Great Qur’an. An example of this is that the sheikh - may God Almighty have mercy on him - when he explained the word “intendence” in his saying, Glory be to Him, that is, he feared fornication, which is originally the breaking of bones after algebra, so he borrowed for every hardship and harm greater than the agreement of the name with the most obscene abominations. in the calf. As for the last goal of this article about searching for the language in its grammar, its morphology and the meanings of each vocabulary of it.